2020
DOI: 10.1155/2020/4768390
|View full text |Cite
|
Sign up to set email alerts
|

Potential Biomarkers of Peripheral and Central Fatigue in High-Intensity Trained Athletes at High-Temperature: A Pilot Study with Momordica charantia (Bitter Melon)

Abstract: Among potent dietary supplements, Momordica charantia, commonly called bitter melon, has various biological effects, such as antioxidant and anti-inflammatory effects, and improves energy metabolism and fatigue recovery. However, it is unknown whether Momordica charantia extract (MCE) induces antifatigue effects during exercise training in high-temperature environments. This study aimed at investigating the efficacy of MCE by examining 10 male tennis players consuming 100 mL MCE/dose (6 times a day over 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The KME group was administered an additional 110 mL of mistletoe extract before and immediately following the 2,000 m rowing exercise, prior to blood collection. Mistletoe extract was prepared according to a method validated in previous studies on natural plants [ 28 , 29 ]. The specific manufacturing process is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The KME group was administered an additional 110 mL of mistletoe extract before and immediately following the 2,000 m rowing exercise, prior to blood collection. Mistletoe extract was prepared according to a method validated in previous studies on natural plants [ 28 , 29 ]. The specific manufacturing process is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown that the MCE supplementation induces positive effects on fatiguerelated hormones in response to a high-temperature environment combined with high-intensity training. (16) In this study, a significant enhancement of flexibility, cardiorespiratory function, and balance in pre-post design paired test of MCE supplementation were observed in the subjects that included elite tennis players (Table 1), suggesting that MCE supplementation could benefit a diverse range of physical fitness and adequate recovery through its anti-fatigue effects.…”
Section: Discussionmentioning
confidence: 55%
“…As previously noted, M. charanitia showed anti-stress effects in animal studies. Recently, we found that M. charanitia extract (MCE) supplementation induced anti-fatigue effects on high-intensity trained athletes, resulting in significant regulation in central fatigue-related hormone release, ( 16 ) which is warranted to further investigate its influence on stress-related hormonal response, particularly in the circulating plasma levels of ACTH and cortisol.…”
Section: Introductionmentioning
confidence: 99%
“…Swimming exercises were carried out 3 times in a week for 4 weeks with an intensity of 6% of body weight and the duration was 70% of maximum time (Prasetya et al, 2018). Morning swimming exercise was held at 08.00-09.00 AM, while night swimming exercise was held at 20.00-21.00 PM (Pranoto et al, 2020;Kwak et al, 2020). The mice were given intervention of moderate-intensity swimming exercise in the morning and at night, with water temperature maintained at 30 ± 2°C (Wierzba et al, 2006).…”
Section: Protocol Of Exercisementioning
confidence: 99%